2010
DOI: 10.1364/oe.18.003883
|View full text |Cite
|
Sign up to set email alerts
|

Multiple and dependent scattering effects in Doppler optical coherence tomography

Abstract: Doppler optical coherence tomography (OCT) is a technique to image tissue morphology and to measure flow in turbid media. In its most basic form, it is based on single (Mie) scattering. However, for highly scattering and dense media multiple and concentration dependent scattering can occur. For Intralipid solutions with varying scattering strength, the effect of multiple and dependent scattering on the OCT signal attenuation and Doppler flow is investigated. We observe a non-linear increase in the OCT signal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
46
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 24 publications
4
46
0
Order By: Relevance
“…Intralipid is an aqueous suspension of polydisperse lipid droplets, which is often used as a tissue phantom for optical measurements. Recently we showed that for high Intralipid concentrations multiple and dependent scattering effects play an important role and lead to nonlinear changes in the scattering coefficient with concentration [11]. To avoid these effects, measurements with low concentrations Intralipid (0.63, 1.25 and 2.5 wt.%) are performed.…”
Section: Scattering Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Intralipid is an aqueous suspension of polydisperse lipid droplets, which is often used as a tissue phantom for optical measurements. Recently we showed that for high Intralipid concentrations multiple and dependent scattering effects play an important role and lead to nonlinear changes in the scattering coefficient with concentration [11]. To avoid these effects, measurements with low concentrations Intralipid (0.63, 1.25 and 2.5 wt.%) are performed.…”
Section: Scattering Samplesmentioning
confidence: 99%
“…The scattering anisotropy plays an important role in diffusive light transport, for example in diffuse reflectance spectroscopy. Also in OCT, g plays an important role as it determines the amount of backscattering and in the quantification of multiple scattering effects in (Doppler) OCT [11]. The possibility to extract g from OCT measurements is very attractive, because, in comparison with commonly used goniometric or integrating sphere methods, the non-invasive nature of OCT allows for in-vivo application.…”
Section: Introductionmentioning
confidence: 99%
“…14 More recently, Mie theory and the extended Huygens-Fresnel (EHF) model have been used to model scattering. [15][16][17][18] These models have enabled quantification of tissue optical properties and highlight the non-linearity of OCT signal with increasing scatterer concentration. However, these models require the adjustment of many parameters and are limited in fundamental physical scope by the assumptions of Mie scattering.…”
mentioning
confidence: 99%
“…1. Light from a broadband source (B&W Tek superluminescent diode, λ c ¼ 1300 nm, 40 nm FWHM, 7 mW output power) is coupled, via an optical circulator (Gould Fiber Optics), into a 90=10 beam splitter with polarization controllers positioned in both the sample and reference arms [10]. The backreflected light is redirected through the optical circulator and coupled into the input waveguide of the AWG spectrometer.…”
mentioning
confidence: 99%